de l’argument ad hominem dans les débat politique français Le cas du débat de l’entre deux-tours de l’élection présidentielle de 2012 entre Nicolas Sarkozy et François Holland - htalbi, chik (El Omda in Linguistics and Discourse Analysis, 2018)
This article focuses on an analytical study of the final face-off between the two remaining candidates, François Hollande and Nicolas Sarkozy, during the French presidential election held on May 2, 2012. This study guides us in analyzing how the presidential candidates used fallacious reasoning strategies in order to persuade the audience of their views during their interaction in this debate and to encourage them to trust their arguments. Among these strategies, the “ad hominem” argument, which is often misleading, is used to attack the opponent and refute their evidence by focusing on flaws in their personality or behavior. The aim of this study is to analyze these various ad hominem-based arguments and evaluate them in the candidates’ speeches during this crucial debate prior to the actual election.